Frontispiece: Halogen Bonding Helicates Encompassing Iodonium Cations. Issue 27 (24th June 2019) - Vanderkooy, Alan; Gupta, Arvind Kumar; Földes, Tamás; Lindblad, Sofia; Orthaber, Andreas; Pápai, Imre; Erdélyi, Máté
Abstract : Halogen Bonds In their Communication on page 9012 ff., M. Erdélyi and co‐workers present iodonium cations that are stabilized by three‐center, four‐electron [N−I−N] + halogen bonds with oligomeric pyridyl ligands.